Dam seepage assessment based on combined electrical resistivity tomography and environmental isotope techniques at Machap Reservoir, Malaysia - Mejus, Lakam; Asfahani, Jamal; Mohd Hashim, Mohd Muzamil; Yaccup, Rahman; Mustaffa, Mohamad Syahiran; Gerusu, Geoffery James (EM International, 2021)
Most of the earthen dams around the world unfortunately suffer from common filtration or leakage problems, which may occur either through the bedrock of damâs lake or through the dam body foundations. The dam seepage assessment normally is determined based on a single method to generate seepage pathway. However, the commonly used approach such as geophysical method has yet to be satisfactorily yield reliable results by most of the developing countries including Malaysia. This study aimed to provide reliable and vital data on dam seepage problem based on combination of Electrical Resistivity Tomography (ERT) and environmental isotopes approaches. ERT was applied to characterize the subsurface soil materials within the wetness area and environmental isotope approach was used to determine the water origin. This study was conducted at Machap dam in Peninsular Malaysia. The 2D inversion results based on ERT showed a contrasting resistivity values suggest a one-layer structure model with solid backfill materials on the surface. The most prominent feature in the vertical sections is the clear contrast between the conductive unit (<100 ïm) and resistive unit (>100 ïm). The conductive unit is distinctly continuous thick layering with the depth varying from 8 m to 30 m, indicative of potential water saturated zone or recharge pathways. The isotope ratio data revealed that the wetness area or of the natural ground is identical to the groundwater component and far different from that of Machap reservoir water. It is indicated that the wetness area can be associated with groundwater origin and is probably controlled by the natural topography of the groundwater contours and drainage characteristics of the soil media. The study verified that a combination of ERT-environmental isotope approaches able to assess dam seepage effectively and more reliable.